Chemoselective hydrogenation of heteroarenes and arenes by Pd–Ru–PVP under mild conditions. Issue 72 (15th December 2020) - Chaudhari, Chandan; Sato, Katsutoshi; Nishida, Yoshihide; Yamamoto, Tomokazu; Toriyama, Takaaki; Matsumura, Syo; Ikeda, Yasuyuki; Terada, Kenji; Abe, Naoya; Kusuda, Kohei; Kitagawa, Hiroshi; Nagaoka, Katsutoshi
Abstract : Recyclable Pd0.5 Ru0.5 –PVP catalyst showed higher activity than monometallic Pd or Ru catalyst for the hydrogenation of quinoline. Furthermore, Pd0.5 Ru0.5 –PVP was able to hydrogenate different arenes. Abstract : Monometallic (Pd, Ru or Rh) and bimetallic (Pd0.5 –Ru0.5 ) alloy NPs catalysts were examined for the hydrogenation of quinoline. Pd–Ru alloy catalyst showed superior catalytic activity to the traditional Rh catalyst. The characterization of Pd0.5 –Ru0.5 catalysts, HAADF-EDX mapping and XPS analysis suggested that the alloy state of PdRu catalysts remained unchanged in the recovered catalyst. Furthermore, the catalyst was highly selective for the hydrogenation of different arenes.